Utilização de metaheurísticas combinada a diferentes métodos de aglutinação para a otimização de um processo de torneamento com múltiplas respostas - Penteado, Ricardo Batista [UNESP] (2015)
The nickel-based alloys have a chemical composition with high content of alloying elements, which are responsible for their mechanical and thermal properties, but these features interfere in the machining. Its widespread use in these areas is mainly due to its performance at high temperatures, which is given by some of its characteristics, such as high mechanical strength at elevated temperature, creep, fatigue and corrosion resistance. The objective of this work was to study and evaluate the machining process by external cylindrical turning of the nickel alloy based Nimonic 80A and propose new ways of thinking in multiple response optimization process using different search methods and different methods of agglutination from modeling process. To this, the variables analyzed were: surface roughness (Ra) and cut length (Lc). The machining tests were performed on a CNC lathe, being considered the following machining parameters: cutting speed (75 and 90 m / min), depth of cut (0.8 and 1.6 mm) and feed rate (0.12 and 0.18 mm/revolution), TP2500 and CP250 tools, test body made of Nimonic 80A material hot rolled and annealed and Fluid Lubricant varying amount in Minimal Quantity of Fluid (MQF) and abundant. The whole process was conducted in cycles where each cycle ended when it reached the maximum feed length (Lf). The entire process was conducted in cycles, wherein each cycle ended when it reached the maximum feed length (Lf). After performed the process modeling, were used GRG algorithm, three different meta-heuristics and 4 different agglutination methods and evaluated. To evaluate the performance of meta-heuristics and agglutination methods we used the method of Taguchi L16, reaching the conclusion that all showed significance in the proposed evaluation, and the methods tested here showed efficiency for such research